Can R&D Transfer and Market Openness Improve the National Export Rate? A Global Entrepreneur Perspective - Devani Nariratya Putri; Iwan Hermawan; Achmad Zaenuddin (Journal of Governance Risk Management Compliance and Sustainability, 2023)
R&D Transfer gives birth to an understanding of the importance of the role of the latest applied research in developing entrepreneurs to compete in the global market. The global market that continues to be dynamic allows the emergence of various access restrictions that make it difficult for entrepreneurs, so the existence of market openness is needed as an entry point for entrepreneurs into the global market. This study aims to solve the gap of a significant decrease in world export levels in 2020 by 2.1%. This problem is considered crucial because this is the worst decline in the last decade. The data in this study was taken through secondary data from the Global Entrepreneurship Monitor (GEM) and the World Bank from various countries on five continents in the 2019-2021 data period. The data is processed using Structural Equation Modeling (SEM) analysis instruments. This study empirically requires that the existence of R&D Transfer can encourage market openness to increase the export rate with a direct effect of 0.577. Thus, R&D Transfer has proven to be able to create new applied research and technology that encourages the creation of market openness for entrepreneurs so that they can compete in the global market and lead to an increase in the National Export Rate. Therefore, the practical implications of this study show that countries need to encourage the existence of R&D Transfer through the fulfillment of Physical Infrastructure and Government Support to increase market opening for increased exports.